1965
DOI: 10.1128/jb.90.3.571-574.1965
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemistry of the Group-Specific Polysaccharide of Nocardia brasiliensis

Abstract: of the group-specific polysaccharide of Nocardia brasiliensis. J. Bacteriol. 90:571-574. 1965.-The groupspecific polysaccharide of Nocardia brasiliensis was further purified, yielding an amorphous white material with the following characteristics: [a]D20 = + 48; nitrogen, 0.5%; phosphorus, 0.1%; and ash as sodium, 0.8%. The polymer is made of D-arabinose and D-galactose in a molar ratio of 3:1, and no other sugars were detected. Mild hydrolysis liberates mainly arabinose. The polysaccharide consumes 3.46,umole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Nocardia and Mycobacterium have also been studied with serological methods such as agglutination, complement fixation, and sensitin tests as well as with immunodiffusion and immunoelectrophoresis. In these studies it has been shown that various species of Nocardia and Mycobacterium have antigens in common (1,3,7,10,11,13,14,26,27,42). Furthermore, with serological methods it has been possible to distinguish different species within the genus Nocardia (31, 32,41,46,51).…”
mentioning
confidence: 99%
“…Nocardia and Mycobacterium have also been studied with serological methods such as agglutination, complement fixation, and sensitin tests as well as with immunodiffusion and immunoelectrophoresis. In these studies it has been shown that various species of Nocardia and Mycobacterium have antigens in common (1,3,7,10,11,13,14,26,27,42). Furthermore, with serological methods it has been possible to distinguish different species within the genus Nocardia (31, 32,41,46,51).…”
mentioning
confidence: 99%